Basketball free-throws performance depends on the integrity of binocular vision - Vera, J.; Molina, R.; Cárdenas, D.; Redondo, B.; Jiménez, R. (European Journal of Sport Science, 2020)
Background: The deterioration of the integrity of binocular vision has a detrimental effect on fine visuomotor skills, however, its impact on sports performance remains unknown. We tested the influence of four viewing conditions (binocular viewing, monocular viewing, binocular viewing with monocular blur, and binocular viewing with binocular blur) on basketball free-throws performance.